A radar study of squall lines affecting Nagpur airport - CHOWDHURY, A.; NAIR , K. G. S.; BANERJEE, A. K. (MAUSAM, 1976)
The paper presents results of detailed study of squall lines that formed and affected Nagpur airport during 1961-1970. Some characteristic features of these lines have been discussed. The rough terrain of Satpura mountain range appears to be favourable for initial formation of echoes resulting in the organisation of line. Relation between computed normal motion of the line from 700 mb and the actual motion has been brought out.